Tingkat Pengetahuan Pasangan Usia Subur tentang Kontrasepsi di RW XI Desa Makamhaji Kecamatan Kartasura - Yovita Dewi Septya Adi; Retnowati Adiningsih (Indonesian Journal on Medical Science, 2023)
In Indonesia, couples of childbearing age who use contraceptive methods continue to increase, reaching 61.4%. According to Pattypeilohy's (2018) survey in Kupang, 57 persons (or 57% of the population) had little to no understanding about contraception. Couples of reproductive age often choose not to utilize contraceptive techniques because they are unaware of its effectiveness and how it may affect their behavior, attitudes, motivation, and actions surrounding pregnancy. Each method has advantages and disadvantages. Many women find that using contraception is sometimes problematic and may be forced to choose an inappropriate method with harmful consequences or not use a method at all. This research sought to ascertain the amount of information that couples in RW XI Makamhaji Village, Kartasura District, had about contraception. The research tool for this study is a closed-ended questionnaire, which is part of a quantitative descriptive methodology. Couples in RW XI Makamhaji Village, Kartasura District, who were of reproductive age made up the sample for this research, which included 110 participants. According to the study's findings, 67 participants (60.9%) had high knowledge, 27 participants (24.5%), adequate knowledge, and 16 participants (14.5%), less understanding.